Auction of Banking Credit Guarantees for Debtors Who Default on Credit Agreements - Magdalena Ermiyanti Sinaga; Amad Sudiro (Greenation International Journal of Law and Social Sciences, 2024)
This research discusses the problem of debtor default on credit agreements which results in an auction process for debtor credit guarantees by the bank to pay off (return) the money loan along with fines and other costs which should be the debtor's obligations based on the credit agreement. In this research, the object of research is the DKI Jakarta High Court Decision Number 454/PDT//2018/PT.DKI. In this decision, the debtor who entered into a credit agreement with the bank and based on the descriptions as outlined in the lawsuit letter has fulfilled the elements of default. The element of default that has been fulfilled is the debtor's inability to make credit payments to the bank as agreed in the credit agreement. In connection with this default, the bank has issued a summons (reprimand) 3 (three) times in a row. Because the debtor did not heed the summons (warning) letter, the bank finally took the initiative to hold an auction for part of the credit guarantee from the debtor. However, because the debtor felt injustice regarding the credit guarantee auction, the debtor filed a lawsuit against the law against the bank through the Central Jakarta District Court. This research aims to examine defaults made by debtors in credit agreements which result in banks auctioning debtor collateral. It is hoped that the results of this research will be useful for stakeholders in credit agreements to provide an overview of the legal consequences of credit guarantees if a default occurs.